Pediatric-onset limited ANCA-associated vasculitis arising during pre-existing chronic recurrent multifocal osteomyelitis - Esraa Eloseily; Michael Henrickson (BMC, 2023)
Abstract Background Granulomatosis with polyangiitis (GPA) is an autoimmune disease characterized by chronic vasculitis involving small to medium sized arteries, granulomatous inflammation of the upper and lower respiratory tracts, pauci-immune necrotizing glomerulonephritis, as well as vasculitis of other organs. Chronic recurrent multifocal osteomyelitis (CRMO) is an autoinflammatory syndrome characterized by sterile bone inflammation. Case presentation We report a case of CRMO that was doing well on non-steroidal anti-inflammatory drugs (NSAID for 6 years and then developed ANCA positive limited GPA presenting with pyoderma gangrenosum, persistent bilateral otalgia with serous otitis, otorrhea, then sensorineural hearing loss. Conclusion This is the first report of limited GPA initially presenting as pyoderma gangrenosum in a patient with underlying CRMO. It is unclear how the pathology of an autoimmune and an autoinflammatory condition can overlap.